Algae blooms: how can they be harmful to the ecosystem? / Nurshahirah Rahizar ... [et al.] - Rahizar, Nurshahirah; Abdul Aziz, Nur Syawanie; Jamaludin, Siti Nur Syifaa; Shukor, Siti Nur Shazwani; Abd Malek, Alyssa Safiyah; Hisham, Nur Hafizah; Noor Hisham, Aida Qasrina; Kamaruddin, Sharir Aizat; Hashim, Aimie Rifhan (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Algae bloom or algal bloom is an excessive growth of microscopic algae or algae-like bacteria in fresh, salt, or brackish water (Image 1). Algal blooms come in a variety of colors, such as pink, red, brown, yellow, and blue-green (Image 2). A paint-like slick, foam, froth, or bad-smelling scum can result from an algal bloom and it depends on the kind of bacteria or algae that caused it (Denchak, 2019). Not all algae blooms are toxic but a harmful algae bloom or HAB is a bloom that produces toxins. The toxin can be dangerous to humans and other organisms in aquatic ecosystems such as in oceans, ponds, lakes, and freshwater. According to the National Institute of Environmental Health Sciences (2023), certain blooms are easy to identify while others are difficult to identify because they grow near the bottom of water bodies.